2015
DOI: 10.13189/ujp.2015.030403
|View full text |Cite
|
Sign up to set email alerts
|

Hearing, Deaf and Cochlear Implanted Adolescent Males' Social Confidence (C.I. Males are not Confident in the Presence of Deaf Males)

Abstract: We examined differences between Deaf, Cochlear Implanted (CI) and hearing male adolescents in terms of their social confidence levels. 54 Deaf, CI user and hearing male adolescents completed a version of the Deaf Acculturation Scale (DAS) that was specifically designed for adolescents by Maxwell-McCaw and the Jackson Personality Inventory. There was a significant main effect of hearing and deaf environment and hearing environment and general social confidence, but no significant interaction between environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Implants can help deaf individuals improve their hearing but cannot cure deafness and some children may hold unrealistic expectations for themselves resulting in later feelings of low poor self-esteem and disappointment [18]. Berry and O'Rourke [38] explored Deaf, cochlear implanted and hearing male adolescents' differences in social confidence levels and found implant users demonstrated lower social confidence especially when in the company of Deaf males. Irrespective of age, individuals benefit from implants including those who are over 65 [39].…”
Section: Cochlear Implantmentioning
confidence: 99%
See 2 more Smart Citations
“…Implants can help deaf individuals improve their hearing but cannot cure deafness and some children may hold unrealistic expectations for themselves resulting in later feelings of low poor self-esteem and disappointment [18]. Berry and O'Rourke [38] explored Deaf, cochlear implanted and hearing male adolescents' differences in social confidence levels and found implant users demonstrated lower social confidence especially when in the company of Deaf males. Irrespective of age, individuals benefit from implants including those who are over 65 [39].…”
Section: Cochlear Implantmentioning
confidence: 99%
“…Van Eldik [72] reported that Dutch Deaf adolescents in Schools for the Deaf experienced more withdrawn behaviors than their deaf mainstreamed and hearing peers and that experiencing regular interactions in a mainstream school is likely to improve social confidence. In various environmental conditions, adolescents with different hearing status displayed diverse levels of social confidence [38]. In today's Society, it is becoming less frequent for children to engage in initial face-to-face communications because they are increasingly using social media instead.…”
Section: Social Identity/interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, only some studies report primary language use, while none of the studies reported when the participants were first identified as DHH, nor whether they received early educational intervention. Second, the participants were either teenagers in separate high schools for deaf students (Berry & O’Rourke 2015), adults in universities that have high enrollments of deaf students (Marschark et al 2018, Marschark et al 2017; Nelson Schmitt & Leigh 2015), or were recruited from organizations that are organized by and for deaf adults (Nelson Schmitt & Leigh 2015).…”
Section: Acculturationmentioning
confidence: 99%
“…Several studies have used the DAS (Maxwell-McCaw & Zea 2011) in the last few years to measure acculturation in specific populations, finding varied results. For example, Berry and O’Rourke (2015) investigated 34 teenaged males who were DHH (mean age = 17 years) and who attended a separate high school for deaf students in the U.K. They measured the students’ acculturation to a deaf community, hearing community, both communities, or no community using the DAS.…”
Section: Acculturationmentioning
confidence: 99%